Spironolactone and XPB: An Old Drug with a New Molecular Target - Ryan D. Gabbard; Robert R. Hoopes; Michael G. Kemp (Biomolecules, 2020)
Spironolactone (SP) is commonly used for the treatment of heart failure, hypertension, and complications of cirrhosis by antagonizing the mineralocorticoid receptor. However, SP also antagonizes the androgen receptor, and thus SP has also been shown to be effective in the treatment of acne, hair loss, and hirsutism in women. Interestingly, recent drug repurposing screens have identified new and diverse functions for SP as a simulator of tumor immunosurveillance and as an inhibitor of DNA repair and viral infection. These novel pharmacological effects of SP have all been linked to the ability of SP to induce the rapid proteolytic degradation of the xeroderma pigmentosum group B (XPB) protein. XPB is a critical enzymatic component of the multi-subunit complex known as transcription factor II-H (TFIIH), which plays essential roles in both DNA repair and the initiation of transcription. Given the critical functions for XPB and TFIIH in these processes, the loss of XPB by SP could lead to mutagenesis. However, the ability of SP to promote cancer stem cell death and facilitate immune recognition may counteract the negative consequences of SP to mitigate carcinogenic risk. Thus, SP appears to have new and interesting pharmacological effects that may extend its potential uses.